2013
DOI: 10.1002/eet.1622
|View full text |Cite
|
Sign up to set email alerts
|

Evolutions in E‐governance: Evidence from Spanish Local Governments

Abstract: This paper analyzes the development of e‐government, both as an overall process and in each of the three stages identified in the prior literature (e‐government, e‐governance and e‐democracy) in order to determine the expansion of the use of e‐government with the purpose of encouraging citizens' engagement and ability to obtain public services and exchange information with their government online. The analysis has focused on 102 Spanish municipalities, which allow us a more homogeneous comparative analysis. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 42 publications
0
7
1
Order By: Relevance
“…The analysis has shown that the implementation of such forms of participation is still at the beginning, an assessment that has recently been shared by other observers (García‐Sánchez et al ., ). We hope that this article will contribute to devoting more attention to this potentially useful venue of participation that will most probably gain importance in the future.…”
Section: Discussionmentioning
confidence: 97%
“…The analysis has shown that the implementation of such forms of participation is still at the beginning, an assessment that has recently been shared by other observers (García‐Sánchez et al ., ). We hope that this article will contribute to devoting more attention to this potentially useful venue of participation that will most probably gain importance in the future.…”
Section: Discussionmentioning
confidence: 97%
“…National policies, such as the PPCDAm, are a critical means of generating ‘transparency and stakeholder engagement’ among state and municipal governments (García‐Sánchez et al , , p. 337). Yet beyond monitoring, the most important legal mechanism to promote transparency has been Brazil's sweeping FOI law (12.527/2011).…”
Section: The Challenge Of Transparency In Subnational Forest Governancementioning
confidence: 99%
“…There seems to be a growing need from a policy and planning view, but there are also possibilities for governance, to include community preferences and to engage citizens in the creation and development of urban natural resources through the use of e-tools [26][27][28][29][30]. E-tools can seemingly facilitate new forms of knowledge sharing and communication [31][32][33], as they can be used to gather detailed place-based information, citizens and expert knowledge, and facilitate dialogue between varieties of stakeholders [5,[34][35][36][37][38].…”
Section: The Potential Of E-tools In An Ugi Governance Perspectivementioning
confidence: 99%